If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(2x + 6) = 2x + -24 Reorder the terms: 3x + -1(6 + 2x) = 2x + -24 3x + (6 * -1 + 2x * -1) = 2x + -24 3x + (-6 + -2x) = 2x + -24 Reorder the terms: -6 + 3x + -2x = 2x + -24 Combine like terms: 3x + -2x = 1x -6 + 1x = 2x + -24 Reorder the terms: -6 + 1x = -24 + 2x Solving -6 + 1x = -24 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -6 + 1x + -2x = -24 + 2x + -2x Combine like terms: 1x + -2x = -1x -6 + -1x = -24 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 + -1x = -24 + 0 -6 + -1x = -24 Add '6' to each side of the equation. -6 + 6 + -1x = -24 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = -24 + 6 -1x = -24 + 6 Combine like terms: -24 + 6 = -18 -1x = -18 Divide each side by '-1'. x = 18 Simplifying x = 18
| 8h=40 | | 2(-7v-8)=-86 | | 8B=-5+8B | | 2j=56 | | 25x+-45=180 | | 2(-2c-9)= | | 43=k-14 | | 3+2=-7 | | 7(5k+2)= | | 525+0.21d=585+0.13d | | 8x+3+4x=90 | | X^2-8x+12=24 | | -8(4m-9)= | | y^2=20-x^2 | | 8g-6g=8 | | 2x+1-x=-12 | | -w+173=3 | | 246=193-v | | 233-u=127 | | 49x^8+42x^4+9=f(x) | | 36-3w=w | | 7(6k-4)+3k=-388 | | 4x=5(3) | | 14x-16=124 | | 6v=4v+16 | | solvem-3.41=10.7 | | 4w=35-3w | | -4.1-9.12= | | 14u-49= | | 6(-8g+2)= | | -7v=-14 | | -4u=32 |